2012
DOI: 10.1111/j.2153-9588.2012.01094.x
|View full text |Cite
|
Sign up to set email alerts
|

Applying Nepali Ethnopsychology to Psychotherapy for the Treatment of Mental Illness and Prevention of Suicide Among Bhutanese Refugees

Abstract: Addressing mental health needs of 100,000 ethnic Nepali Bhutanese refugees relocated from Nepal is a new challenge for mental health clinicians in the receiving countries. A limitation of current services is the lack of knowledge about cultural understandings of mental health. Ethnopsychology is the study of emotions, suffering, the self, and social relationships from a cultural perspective. Nepali ethnopsychology can be used to develop and adapt mental health interventions for refugees. We discuss applying et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 82 publications
1
44
0
Order By: Relevance
“…These relationships were independent of demographic characteristics (age, sex, ethnic status, low caste, and education) and individual differences in leukocyte subset prevalence. They also emerged in a cultural context that is likely more collectively orientated than populations previously studied in social genomics literature (36)(37)(38). Despite this collective social orientation, individual self-perceptions of personal psychological resilience were associated with markedly lower CTRA gene expression profiles, to the extent that PTSDaffected former child soldiers with high levels of self-reported resilience showed molecular profiles comparable to those of PTSDfree civilian youth.…”
Section: Discussionmentioning
confidence: 94%
“…These relationships were independent of demographic characteristics (age, sex, ethnic status, low caste, and education) and individual differences in leukocyte subset prevalence. They also emerged in a cultural context that is likely more collectively orientated than populations previously studied in social genomics literature (36)(37)(38). Despite this collective social orientation, individual self-perceptions of personal psychological resilience were associated with markedly lower CTRA gene expression profiles, to the extent that PTSDaffected former child soldiers with high levels of self-reported resilience showed molecular profiles comparable to those of PTSDfree civilian youth.…”
Section: Discussionmentioning
confidence: 94%
“…Explanatory models include perceptions of symptoms, etiology, and treatment seeking behaviors. Use of explanatory models and ethnopsychology (local psychological concepts) is a crucial aspect of adapting PT across cultural settings (Hinton, Hofmann, Pollack, & Otto, 2009; Kohrt et al, 2012b). A recent meta-analysis of cultural adaptation of PT found that use of explanatory models, also known as “illness myths”, was the sole moderator of superior outcomes for culturally-adapted therapies (Benish, Quintana, & Wampold, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…These concepts have been used in cultural adaptation of cognitive behavior therapy and other psychological treatments in Nepal and for ethnic Nepali Bhutanese refugees (Kohrt, Maharjan, Timsina, & Griffith, 2012b). …”
mentioning
confidence: 99%
“…Individuals with prior attempts were viewed as having reduced potential for marriage, and, along with relatives, were likely to face discrimination in social and economic sectors. Local ethnopsychological models consider suicide to result from an imbalance or dysfunction of the dimaag (brain-mind), the rational apparatus that governs cognitions as well as proper social functioning (Kohrt, Maharjan, Timsina, & Griffith, 2012). Since dimaag -related problems are considered severe and permanent, they are often associated with profound stigma (Kohrt & Harper, 2008).…”
Section: Resultsmentioning
confidence: 99%